2005
DOI: 10.1080/01496390500385129
|View full text |Cite
|
Sign up to set email alerts
|

Strontium and Actinide Separations from High Level Nuclear Waste Solutions Using Monosodium Titanate 1. Simulant Testing

Abstract: High-level nuclear waste produced from fuel reprocessing operations at the Savannah River Site (SRS) requires pretreatment to remove Pu. This paper provides a summary of data acquired to measure the performance of MST to remove strontium and actinides from simulated waste solutions. These tests evaluated the influence of ionic strength, temperature, solution composition and the oxidation state of plutonium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 15 publications
(12 reference statements)
1
47
0
Order By: Relevance
“…7 2.2 Tank 48H Simulant A simplified Tank 48H simulant solution was prepared following the standard recipe, 8 omitting the solids and organics. Specifically the following components were omitted: sodium tetraphenylborate (NaTBP), Plutonium/Uranium Extraction (PUREX) sludge simulant, MST, biphenyl, diphenyl mercury, and benzene.…”
Section: Methodsmentioning
confidence: 99%
“…7 2.2 Tank 48H Simulant A simplified Tank 48H simulant solution was prepared following the standard recipe, 8 omitting the solids and organics. Specifically the following components were omitted: sodium tetraphenylborate (NaTBP), Plutonium/Uranium Extraction (PUREX) sludge simulant, MST, biphenyl, diphenyl mercury, and benzene.…”
Section: Methodsmentioning
confidence: 99%
“…The Savannah River Site selected this material for strontium and plutonium removal from high-level waste solutions in the early 1980s as part of the In-Tank Precipitation (ITP) process. SRNL modified the synthesis of the MST to optimize performance and transferred this technology to commercial vendors (Hobbs et al 2005 andPeters et al 2006]. Figure 11 shows a Scanning Electron Microscope (SEM) image of MST particles.…”
Section: Monosodium Titanatementioning
confidence: 99%
“…8,9 Historically, sodium titanates have been produced using both sol-gel and hydrothermal synthetic techniques resulting in fine powders with particle sizes ranging from a few to several hundred microns. 4,5,10,11 More recently, synthetic methods have been reported that produced nanosize titanium dioxide, metal-doped titanium oxides, and a variety of other metal titanates. Examples include sodium titanium oxide nanotubes (NaTONT) or nanowires by reaction of titanium dioxide in excess sodium hydroxide at elevated temperature and pressure, [12][13][14] sodium titanate nanofibers by reaction of peroxotitanic acid with excess sodium hydroxide at elevated temperature and pressure, 15 and sodium and cesium titanate nanofibers by delamination of acid-exchanged micron-sized titanates.…”
Section: Introductionmentioning
confidence: 99%